Association of a history of depression with infertility, miscarriage and stillbirth: a longitudinal cohort study - Chen Liang; Hsin-Fang Chung; Annette J. Dobson; Gita D. Mishra (Cambridge University Press, 2024)
Abstract Aims The role of depression in subsequent infertility, miscarriage and stillbirth remains unclear. This study aimed to examine the association of a history of depression with these adverse outcomes using a longitudinal cohort study of women across their reproductive life span. Methods This study used data from participants in the Australian Longitudinal Study on Women's Health who were born in 1973-1978. Participants (N = 8707) were followed up every 3 years from 2000 (aged 22-27) to 2018 (aged 40-45). Information on a diagnosis of depression was collected from each survey, and antidepressant medication use was identified through pharmaceutical prescription data. Histories of infertility, miscarriage, and stillbirth were self-reported at each survey. Time-lagged log-binomial models with generalized estimating equations were used to assess the association of a history of depression up to and including in a given survey with the risk of fertility issues in the next survey. Results Women with a history of depression (excluding postnatal depression) were at higher risk of infertility [risk ratio (RR) = 1.34, 95% confidence interval (CI): 1.21-1.48], miscarriage (RR = 1.22, 95%CI: 1.10-1.34) and recurrent miscarriages (≥2; RR = 1.39, 95%CI: 1.17-1.64), compared to women without a history of depression. There were too few stillbirths to provide clear evidence of an association. Antidepressant medication use did not affect the observed associations. Estimated RRs of depression with infertility and miscarriage increased with age. Conclusions A history of depression was associated with higher risk of subsequent infertility, miscarriage and recurrent miscarriages.